Tantangan dan Dukungan dalam Kesiapan Penerapan Rekam Medis Elektronik di Rumah Sakit - Inda Wulansari; Cahya Tri Purnami; Agung Budi Prasetijo (VISIKES: Jurnal Kesehatan Masyarakat, 2023)
The use of paper-based medical records requires a time-consuming process and had a relatively high risk of data loss compared to electronic-based medical records. This literature review aims to analyze the readiness of electronic medical records in hospitals. The search for journal references was carried out through several sources, namely Pubmed, Google Schoolar, and ScienceDirect with material inclusion criteria according to keywords, namely challenges and support in the readiness of implementing electronic medical records and exclusion criteria, namely the journal was a review article. Based on the search results, 963 articles were obtained which were then selected for up to 10 articles that were included in the discussion. The results showed that the readiness of health workers for the implementation of electronic medical records is still low and appropriate considerations and steps are needed to increase readiness in implementing electronic medical records in hospitals.